Propuesta de gamificación para desarrollar la expresión corporal de niños de 4 años del nivel inicial, Lima, 2020 - Castillo Burgos, Zaira Cristel (2023)
The present research work entitled: Gamification proposal to develop the corporal expression of 4-year-old children of the initial level, Lima, 2020. Its general objective was to explain the gamification proposal to develop the corporal expression of 4-year-old children of the initial level., Lima, 2020._x000D_ It was basic research of proactive descriptive design, we worked with 30 students, from the 4-year-old classrooms of the I.E., "Virgen de la Medalla Milagrosa" and "Semillitas", both from the city of Lima. The synthetic analytic was used as a research method, observation as a technique and to measure the variables, observation guides were used for body expression and gamification after each activity with their respective dimensions._x000D_ It was concluded that the gamification proposal is based on virtual game strategies aimed at the educational field, allowing learning and increasing student motivation, this affects the education of students because it manages to reach them in a different way, using games such as those developed in jclic and gnially, as well as virtual tools such as images, music and videos, which help motivate them to learn more.